(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2024)
Fish, both wild and farmed, face stress factors that alter their homeostasis and ability to adapt in natural and captive environments, putting their survival at risk. Pollution and changes in water quality affect their health and response to stress. In this area, cortisol is a glucocorticoid released by the hypothalamic-pituitary-interrenal axis, which is key in the response to stress and everything related to its survival. The objective of this review was to analyze stress in fish from Latin America and the cortisol response. The analysis showed that the studies have been carried out in Brazil 77%, Colombia 10%, and Ecuador, Mexico, Uruguay and Chile, with 3% respectively. 13 studied species are reported, corresponding to: Brycon amazonicus, B. cephalus, Piaractus mesopotamicus, P. brachypomus, Colossoma macropomum, Rhamdia quelen, Pimelodus maculatus, Oreochromis niloticus, O. mossambicus, Morone saxatilis, Arapaima gigas, Austrolebias reicherti and Salmo salar . The fish species analyzed in Latin America are mostly native, with the main stressors identified being hypoxia, persecution, transportation and handling, which increase cortisol levels. However, the use of additives such as clove oil, β-glucans and ascorbic acid helps reduce this elevation. It is important to note that although chemical anesthetics such as MS-222, although they reduce stress, affect processes such as reproduction. However, the use of essential oils such as clove oil or β-glucans help reduce stress indices, so essential oils could be an alternative without negative effects on some other physiological functions.